2016
DOI: 10.1158/1535-7163.mct-15-1006
|View full text |Cite
|
Sign up to set email alerts
|

BPR1J373, an Oral Multiple Tyrosine Kinase Inhibitor, Targets c-KIT for the Treatment of c-KIT–Driven Myeloid Leukemia

Abstract: Acute myelogenous leukemia (AML) carrying t(8;21)(q22;q22) or inv(16)/t(16;16)(p13;q22) is classified as core binding factor (CBF)-AML and accounts for approximately 15% of AML. c-KIT mutation can be detected in 17%∼46% of CBF-AML and is associated with poor prognosis. c-KIT mutation is a crucial hit and cooperates with AML1-ETO resulting from t(8;21)(q22;q22) to cause overt AML. Tyrosine kinase inhibitors (TKI) targeting c-KIT, such as imatinib, has been used successfully to treat c-KIT driven gastrointestina… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 48 publications
(55 reference statements)
2
15
0
Order By: Relevance
“…Furthermore, BPR1J373 also showed a remarkable potency in the suppression of KIT activation in COS‐1 transfectants with all 4 double mutations, whereas imatinib, sunitinib, nilotinib, and regorafenib showed variable effects on suppression of KIT phosphorylation (Figure B). For D816V in exon 17, which is resistant to imatinib, sunitinib, and nilotinib, BPR1J373 still suppressed KIT phosphorylation in a time‐dependent manner, whereas the other 3 tyrosine kinase inhibitors did not, as shown previously …”
Section: Resultssupporting
confidence: 78%
See 4 more Smart Citations
“…Furthermore, BPR1J373 also showed a remarkable potency in the suppression of KIT activation in COS‐1 transfectants with all 4 double mutations, whereas imatinib, sunitinib, nilotinib, and regorafenib showed variable effects on suppression of KIT phosphorylation (Figure B). For D816V in exon 17, which is resistant to imatinib, sunitinib, and nilotinib, BPR1J373 still suppressed KIT phosphorylation in a time‐dependent manner, whereas the other 3 tyrosine kinase inhibitors did not, as shown previously …”
Section: Resultssupporting
confidence: 78%
“…BPR1J373 also exerted an inhibitory effect on Aurora kinase A and B in GIST882 cells, as shown in , which suggests that the induction of apoptosis in GIST882 might occur through targeting of KIT and possibly Aurora kinase A and B. We have previously shown that BPR1J373 was effective in suppressing phosphorylation of Aurora kinase B and inducing polyploidy of the acute myeloid leukemia cell line KG‐1 . Although BPR1J373 has both anti‐Aurora kinase A and B activity, its inhibition on Aurora kinase A or B might depend on the cellular contents of different cancer cell types.…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations